Virtual focus groups for improved A-Z list user experience - Kraft, Amanda; Scronce, Gretchen; Jones, Allison (The Journal of academic librarianship, 2022)
User focus groups can be a particularly effective way to design user-driven changes to library services. This paper explains how three faculty librarians designed and conducted virtual focus groups to improve the College of Charleston (CofC) Libraries' A-Z Database List; provides analysis of the data gathered via focus group sessions and a follow-up survey; details how this information has been used to make changes for the sake of student user experience (UX) and user interface (UI) design; and shares overall impressions and insights gained from the study. By inviting student participants to explore the list in a setting that was both structured and open-ended, librarians learned what mattered most to students using this resource.